Penerapan Balance Scorecard pada Perguruan Tinggi di Indonesia: Tinjauan Literatur Sistematis - Latifha Aini; Salma Riyanti Hanifah; Fitroh Fitroh (Maranatha University Press, 2023)
By implementing good education, a country can build people's mindsets for more skills and make the country seen and considered by others. The main purpose of writing this paper is to find out how far the benefits of using a balanced scorecard in a university in Indonesia are. Systematic Literature Review is the method used in this study. As time goes by, more and more universities are implementing this balanced scorecard strategy. This balanced scorecard is used as an instrument in measuring the performance of related tertiary institutions. Of the 23 universities discussed in this paper, 82,61% of them use the 4 balanced scorecard perspectives simultaneously. Meanwhile, the rest of the universities only use 3 or even 1 perspective. This is because each tertiary institution has its own concept or arrangement. In addition, there has been a lot of literature showing that the balanced scorecard has various useful values, especially in achieving strategy and improving organizational performance. Based on several studies, the status of the implementation of the balanced scorecard also shows a minimal failure rate and a relatively high success rate. The use of the balanced scorecard is also beneficial for tertiary institutions in knowing their operational performance, with the results of the balanced scorecard, if the score is still not sufficient then the tertiary institution can further improve its quality, which focuses on aspects of value that are not sufficient.